2007
DOI: 10.3892/ijo.30.4.1011
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with MHC class I-negative but not -positive HPV16-associated tumour cells inhibits growth of MHC class I-negative tumours

Abstract: Abstract. Loss or downregulation of MHC class I molecules on tumour cells is a common mechanism by which tumours can escape from T-cell mediated immune responses. In this study we have investigated the immunologic crossreactivity between murine tumour cell lines expressing human papilloma virus (HPV) 16-derived E6/E7 oncoproteins with distinct surface expression of MHC class I molecules. The aims of this study were to demonstrate whether immune responses capable of coping with MHC class I-positive tumours can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
2
12
0
Order By: Relevance
“…In this communication, our previously obtained results (14,15) Collectively, our results indicate an important role of NK1.1 + cells and IFNÁ production by these cells in the induction of the protective immunity against MHC I-deficient HPV16-associated tumours. NK1.1 + cells seem to be an important part of the complex mechanism in development of specific immunity against MHC class I-deficient tumours that includes the cooperation of various cell subsets.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In this communication, our previously obtained results (14,15) Collectively, our results indicate an important role of NK1.1 + cells and IFNÁ production by these cells in the induction of the protective immunity against MHC I-deficient HPV16-associated tumours. NK1.1 + cells seem to be an important part of the complex mechanism in development of specific immunity against MHC class I-deficient tumours that includes the cooperation of various cell subsets.…”
Section: Discussionmentioning
confidence: 66%
“…In our previous studies, it was found that immunization with cellular vaccines based on MHC class I-deficient tumour cells was effective against MHC class I-deficient tumours, as well as against their 'parental' MHC class I-positive tumours, due to the antigen cross-presentation (14). Moreover, we have shown, using the same model, that immunization with peptides, peptide-pulsed DC or MHC class I-deficient tumour cells can elicit specific immunity against these tumours, but the MHC class I expression status has to be considered in optimization of the vaccination strategy (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations